'Literature review on the analysis of climate change risks in the environmental impact assessment of dams'. Issue 4 (4th July 2021) - Loza, Ana Rita Arnaud; Fidélis, Teresa
ABSTRACT: Climate change is a current concern in our society, with consequences increasingly felt worldwide. Alongside territories and communities, large infrastructures such as dams may be vulnerable to climate change and need to be resilient to related impacts. Consequently, their approval should require a comprehensive assessment of associated climate change risks. This concern is addressed by several international guidelines that suggest incorporating the evaluation of climate change risks in the Environmental Impact Assessment (EIA) process to overcome it. It is also evidenced in several national EIA regulations updated accordingly. Based on a systematic review of scientific literature published in the last twenty years, this paper explores how has the scientific community addressed the integration of climate change risks in the EIA of dams. The findings show that the potential of EIA to address climate change risks is widely acknowledged. However, published systematic studies assessing how the analysis of these risks is being included in dams' EIA current practice, are rare. This gap suggests a research potential around the topic and a new niche for research.